On the Future of Congestion Control for the Public Internet - , Lloyd Brown; Ananthanarayanan, Ganesh, Ethan Katz-Bassett, Arvind Krishnamurthy, Sylvia Ratnasamy, Michael Schapira, Scott Shenker (ACM Workshop on Hot Topics in Networks (HotNets), 2020)
The conventional wisdom requires that all congestion control algorithms deployed on the public Internet be TCP-friendly. If universally obeyed, this requirement would greatly constrain the future of such congestion control algorithms. If partially ignored, as is increasingly likely, then there could be significant inequities in the bandwidth received by different flows. To avoid this dilemma, we propose an alternative to the TCP-friendly paradigm that can accommodate innovation, is consistent with the Internet's current economic model, and is feasible to deploy given current usage trends.